Role of miRNA-181a in the treatment of oxaliplatin-induced neuropathy with asprosin: An examination in mouse dorsal root ganglia - Adam, Muhammed; Bulut, Ferah; Dalkilic, Semih; Cimen, Yasin Ali; Ozcan, Mete (Annals of Medical Research, 2024)
Aim: Neuropathic pain, a debilitating condition often resulting from chemotherapy treatments like oxaliplatin (OXA), poses significant treatment challenges. The molecular mechanisms underlying this condition remain incompletely understood, although microRNAs (miRNAs) have been implicated in its pathophysiology. This study focuses on miRNA-181a, known for its role in neuroinflammation and neuron signaling pathways, and investigates the therapeutic potential of asprosin, a novel hormone implicated in metabolic regulation, for modulating miRNA-181a expression in the context of OXA-induced neuropathy.Materials and Methods: Mouse dorsal root ganglia (DRGs) were exposed to OXA to induce neuropathy, followed by treatment with asprosin. miRNA-181a expression levels were quantified and compared across healthy (control), OXA-treated, and asprosin-treated groups using qRT-PCR. Statistical significance was determined through ANOVA, with p-values less than 0.05 considered significant.Results: Asprosin treatment did not significantly affect miRNA-181a expression in healthy mouse DRGs. However, OXA treatment resulted in a significant increase in miRNA-181a expression compared to controls (p
Keywords: Asprosin; miRNA-181a; Oxaliplatin; Neuropathy; Mouse dorsal root ganglia